Dissolved black carbon is not likely a significant refractory organic carbon pool in rivers and oceansAbstract - Qi, Yuanzhi; Fu, Wenjing; Tian, Jiwei; Luo, Chunle; Shan, Sen; Sun, Shuwen; Ren, Peng; Zhang, Hongmei; Liu, Jiwen; Zhang, Xiaohua; Wang, Xuchen (Nature Communications, 2020)
Rivers are the major carriers of dissolved black carbon (DBC) from land to ocean; the sources of DBC during its continuous transformation and cycling in the ocean, however, are not well characterized. Here, we present new carbon isotope data for DBC in four large and two small mountainous rivers, the Yangtze and Yellow river estuaries, the East China Sea and the North Pacific Ocean. We found that the carbon isotope signatures of DBC are relatively homogeneous, and the DBC C-14 ages in rivers are predominantly young and increase during continuous transport and cycling in the ocean. The results of charcoal leaching experiments indicate that DBC is released from charcoal and degraded by bacteria. Our study suggests that riverine DBC is labile and respired during transport and mixing into the ocean and that residual DBC is cycled and aged on the same time scales as bulk DOC in the ocean. Black carbon is a recalcitrant byproduct of biomass burning that ultimately accumulates in oceanic sinks. Here the authors assessed the sources and cycling of dissolved black carbon in rivers and oceans, finding that oceanic pools are cycled and aged on the same time scales as dissolved organic carbon.
Keywords: Changjiang; cycle; flux; HUANGHE RIVERS; level; particulate; quantification; radiocarbon; sea